Consumer Willingness to Pay for Catechin‐enriched Yogurt: Evidence from a Stated Choice Experiment. Issue 2 (2nd September 2014) - Moro, Daniele; Veneziani, Mario; Sckokai, Paolo; Castellari, Elena
ABSTRACT In recent years, food manufacturers have been devoting a large portion of their R&D budgets to the development of functional foods. Although functional foods exhibit a significant level of information asymmetry, consumers appear to be increasingly appreciative, recognizing their role in preventing or reducing health risks and/or improving other physiological functions. This paper quantifies the willingness to pay of a representative sample of 600 Italian consumers for a hypothetical yogurt using a web‐based stated choice experiment. The willingness to pay for two functional attributes (probiotics and catechin enrichment) was measured using the panel data version of a Random Parameters Logit model. The results show that respondents are willing to pay a premium for a catechin‐enriched yogurt (0.38 €/jar), which is well above their willingness to pay for the probiotic attribute (0.21 €/jar). Averaging the individual values across sample sub‐groups indicates that the willingness to pay for catechin enrichment may be related to age, income, health status, lifestyle and education. [EconLit citation: C25, C93, D12]